2013
DOI: 10.1186/1471-2458-13-1034
|View full text |Cite
|
Sign up to set email alerts
|

Early results of an integrated maternal, newborn, and child health program, Northern Nigeria, 2009 to 2011

Abstract: BackgroundThis paper describes early results of an integrated maternal, newborn, and child health (MNCH) program in Northern Nigeria where child mortality rates are two to three times higher than in the southern states. The intervention model integrated critical health systems changes needed to reinvigorate MNCH health services, together with community-based activities aimed at mobilizing and enabling women to make changes in their MNCH practices. Control Local Government Areas received less-intense statewide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Sixty-six eligible studies were identified from 2,662 studies, after applying pre-defined exclusion criteria to the title/abstract and the full text evaluation [ 18 , 20 , 22 , 31 , 49 - 108 ]. Additional file 2 : Table S1 presents a detailed description of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixty-six eligible studies were identified from 2,662 studies, after applying pre-defined exclusion criteria to the title/abstract and the full text evaluation [ 18 , 20 , 22 , 31 , 49 - 108 ]. Additional file 2 : Table S1 presents a detailed description of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…There was multi-centric intervention studies conducted between 2006–2008 [ 60 , 62 ], which produced favourable results about the effectiveness of Magnesium Sulphate in the management of pre-eclampsia. On the other hand there are interventions [ 22 ], which were executed after the development of the integrated maternal, newborn and child health strategy (IMNCH; 2007). On the whole many of the policies have no temporal association with the intervention studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pre-diabetic states are impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and a combination of both (IFG&IGT). Subjects in any of these three pre-diabetic states have moderate to severe insulin resistance, impaired insulin secretion and/or insulin sensitivity, and each state has distinct pathophysiologic etiologies and risks of developing into T2D [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%